Strategies to Improve Mathematics Learning Outcomes Through Flipped Classroom: Strategi Peningkatan Hasil Belajar Matematika Melalui Flipped Clasroom - Nurin Afdillah; Ida Rindaningsih (Academia Open, 2022)
The purpose of this study was to analyze the presence or absence of and how much influence the flipped classroom learning model had on the mathematics learning outcomes of fractions. This research was conducted at MI Nurul Huda Candi Sidoarjo for the 2020/2021 Academic Year. This study uses quantitative research with a sample of 40 students. The data collection after the treatment was carried out using the Mathematics Learning Outcomes Test for fractions. The results showed that there were differences in learning outcomes between students who were taught using the flipped classroom learning model and students who were taught using the conventional learning model with a value (tcount = 2,041 > ttable = 2, 024) at a significance level of 5%. it can be concluded that there is an effect of the flipped classroom learning model on the mathematics learning outcomes of fifth grade students at MI Nurul Huda Candi Sidoarjo. The large influence of the flipped classroom learning model on the mathematics learning outcomes of fifth grade students at MI Nurul Huda Candi Sidoarjo is 6.87%.